2004
DOI: 10.1111/j.1540-8159.2004.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Chest Roentgenogram Predict the Posture Dependent Changes of Atrial Sensing Performance in Patients with a VDD Pacemaker?

Abstract: The VDD pacemaker is useful for sequential pacing with a single lead but carries a risk of sensing failure. This study was designed to evaluate the relationship between the relative position of atrial lead and atrial sensitivity in different postures in patients with VDD pacemakers. Atrial sensitivity determination and chest roentgenography was performed in the supine and standing position 3 months after implantation in 25 patients with VDD pacemakers. Measurements of cardiac longitudinal length (from the top … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Another potential limitation is that P‐wave amplitude measurements were obtained at nighttime between 12 am and 2 am, most likely in a recumbent position. Previous studies using VDD pacemakers showed significant fluctuation of atrial signal with different body positions . However, a recent study using the DX ICD system found comparable range of atrial signal amplitude during various body postures …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another potential limitation is that P‐wave amplitude measurements were obtained at nighttime between 12 am and 2 am, most likely in a recumbent position. Previous studies using VDD pacemakers showed significant fluctuation of atrial signal with different body positions . However, a recent study using the DX ICD system found comparable range of atrial signal amplitude during various body postures …”
Section: Discussionmentioning
confidence: 91%
“…Previous studies using VDD pacemakers showed significant fluctuation of atrial signal with different body positions. 24,25 However, a recent study using the DX ICD system found comparable range of atrial signal amplitude during various body postures. 17…”
Section: Study Limitationsmentioning
confidence: 95%
“…The reliability of this pacing system has been demonstrated in several studies 9,11,12,14,15 . However, due to a great variation of the atrial potential received by free‐floating electrodes 16 and instability of atrial dipole during changes in posture, 17,18 intermittent atrial undersensing remains a potential problem in single‐lead VDD pacing. Many studies have tried to define the predictors of long‐term failure of VDD pacing and to test the effects of new sensing algorithm and dipole design on the incidence of atrial undersensing 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have tried to define the predictors of long-term failure of VDD pacing and to test the effects of new sensing algorithm and dipole design on the incidence of atrial undersensing. 5,6 Recently, Choi et al 17 suggested an interesting technique using chest x-ray for preimplant prediction of posture dependent changes in atrial sensing performance of VDD pacemaker. These efforts have somewhat been effective in the mainte-nance of proper VDD function, but atrial undersensing has persisted.…”
Section: Discussionmentioning
confidence: 99%
“…16 On the other hand, other studies reported that atrial signal amplitudes varied significantly and unpredictably in different postures or maneuvers, even in the same individual. First, posteroanterior CXR gives information about only the position of atrial electrode relative to the lateral atrial wall.…”
Section: Limitationsmentioning
confidence: 99%